Review of challenges and key enablers in energy systems towards net zero target: Renewables, storage, buildings, & grid technologies - Malcolm Isaac Fernandez; Yun Ii Go; Dennis M.L. Wong; Wolf-Gerrit Früh (Heliyon)
Carbon emissions are increasing due to continued urban developments and the growth of the human population, leading to environmental issues such as global warming. Moving towards the future, projected population growth will cause an increase in energy demand. Without the transition to cleaner energy generation, a high dependency on electricity generation by fossil fuels will emit more harmful gases, worsening the impacts of global warming. Therefore, the energy industry is moving towards cleaner alternatives through renewable energy (RE) technologies. However, in the future power grid, more technological development and implementation of cutting-edge research methods will be required to upsurge the percentage of clean electricity generation to attain net zero. Renewables, energy storage systems (ESS), grid technologies, and building energy management systems (BEMS) are key technologies emerging to aid green electrification in the electricity, industry, commercial and transportation sectors. This review discusses the technical challenges and solutions that contribute towards achieving net-zero energy systems. A systematic review was conducted on research methods related to the optimal planning of renewable energy systems, ESS, power system devices, and BEMS which are research areas that are moving towards being optimally integrated in the future energy system. Based on the review, we propose new gaps to be addressed in the development of energy system modelling tools. These tools should seamlessly integrate methods for energy storage related to voltage support, microgrid dispatch strategies, optimal reactive power flow in electrical networks, and energy management in buildings. This integration will enhance the capability of these tools to incorporate detailed analyses into broader energy balance simulations for large geographical regions. This review paper aims to guide researchers in identifying and addressing specific gaps in future research directions within these research areas, thereby advancing the knowledge base and informing subsequent studies.